(untitled) (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2002)
Abstract When Humboldt in 1853 reread his 1804 notebook of his travel from Mexico City to Veracruz, he criticized his “old Neptunistic follies” in a marginal note. Scholars have doubted that he was still a Neptunist in 1804, but this text and Humboldt’s later remark prove it. Curiously, these few pages were omitted from his South American notebooks when they were rebound in 9 volumes at the end of his life. Together with the Berlin State Library autograph collection, these missing pages were relocated during World War II, and for decades they were considered lost. Actually, they are well preserved in the Krakau University Library, where I found them recently. They form a valuable addition to Margot Faak’s edition of Humboldt’s Latin American diaries. This paper discusses the manuscript, showing the development of Humboldt’s opinions in some disciplines he was concerned with. Some of these developments represent paradigmatic changes in natural history, especially in geology. Zusammenfassung Als Humboldt sein 1804 geschriebenes Tagebuch seiner Reise von Mexico City nach Veracruz 1853 nochmals sichtete, schrieb er an den Rand einer Passage die kritischen Worte “Alte neptunistische Verrücktheiten!” Dieser Text und seine spätere Randbemerkung beweisen nun endgültig, daß Humboldt noch gegen Ende seiner Amerikareise Neptunist war, was von Forschern oft bezweifelt worden war. Seltsamerweise hat Humboldt dieses Manuskript nicht mit in die Tagebücher aufgenommen, als er sie gegen Ende seines Lebens in 9 Hefte neu binden ließ. Der Nachlaß Humboldts galt zusammen mit der Autographensammlung der Staatsbibliothek Berlin seit der Auslagerung im zweiten Weltkrieg als verschollen. Er befindet sich heute in Krakau, wo ich diesen Tagebuchteil vor einiger Zeit entdeckte, das nun eine wertvolle Ergänzung zur Edition der Tagebücher durch Margot Faak bildet. Der folgende Text stellt diesen Tagebuchteil vor und zeigt die Entwicklung einzelner Ansichten Humboldts in naturwissenschaftlichen Disziplinen, die z. T. paradigmatische Wandel von Theorien - beispielsweise in der Geologie - anzeigen.